Influence of competitiveness factor towards graduate competency level / Marfunizah Ma’dan, Muhamad Takiyuddin Ismail and Sity Daud - Ma’dan, Marfunizah; Ismail, Muhamad Takiyuddin; Daud, Sity (Universiti Teknologi MARA, 2020)
The intense desire to produce good quality human capital is not sufficient by having basic skills for certain fields only. There is a need to have a competitive attitude to enhance their level of competency as it is a big concern for many employers today. Hence, the study was conducted to identify the competitiveness factors that influence the level of competency among graduates, especially those who are employed in the service sector in Malaysia. This study used the survey method for data collection. Stratified purposive sampling was applied and a questionnaire was distributed to 450 graduates from 13 service sectors based on the statistics obtained from the Ministry of Higher Education 2016. The findings from the exploratory factor analysis found that seven competitiveness factors consisting of 47 items formed the competitiveness attitude among graduates. However, based on a multiple linear regression analysis, only five models of competitiveness factors produced significant relationships with graduates’ competency, which are job competitiveness, organizational management competitiveness, dominant competitiveness, goal competitiveness and self-improvement competitiveness. In fact, aggressive competitiveness and general competitiveness do not influence graduates’ competency level significantly. Therefore, it can be concluded that graduates' competitive attitude such as having emotional control, innovation, and competitive enthusiasm to be the best, is one of the important characteristics for graduate marketability in the future. In addition, it is hoped that their level of competency can be enhanced through the development of competitive factors for the advancement of the country's higher education talents.